Water-Based Polymer Composition and Method for Preparing Same
Patent Information
- Application Number
- JP2023518946
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-10
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2040-10-10
Smart Images

Figure 0007635368000001 
Figure 0007635368000002 
Figure 0007635368000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an aqueous polymeric composition and a method for its preparation.
[0002] Introduction Solvent-based coating compositions containing epoxy, polyurethane, or alkyd resins are widely used in metal protective coatings due to their anticorrosive performance, mechanical properties, and appearance. Water-based acrylic polymer dispersions are much less environmentally fraught than solvent-based dispersions and are typically used for light to moderate metal protection. Black paints, typically containing carbon black as the primary pigment, are widely used in machinery and equipment accessory coatings. Ball mills or sand mills have traditionally been used to produce black paints by dispersing carbon black. Carbon black is more difficult to wet and disperse well in water by conventional dispersion processes alone than inorganic pigments such as titanium dioxide due to its hydrophobic and low density properties. To facilitate the wetting and dispersion of carbon black, large amounts of hydrophilic additives are typically added to black paints, which impairs the anticorrosive performance of the resulting paint. Therefore, improving the corrosion resistance of black paints is more difficult than paints of other colors. In addition, direct-to-metal (DTM) coatings, especially in rainy regions, also need sufficient water resistance to avoid rain-induced blistering, which can also have a negative impact on appearance and corrosion protection performance.
[0003] There is therefore still a need to provide aqueous polymer compositions that are particularly suitable for coatings having the above-mentioned anticorrosive properties. Summary of the Invention
[0004] The present invention provides a novel water-based polymer composition that is free of the above problems and is particularly suitable for coating applications. The water-based polymer composition of the present invention comprises a novel combination of a specific emulsion polymer and a specific water-based resin. The water-based polymer composition can provide coatings, including black paints, with excellent corrosion resistance, characterized by a maximum creep of 2 millimeters (mm) at the scribe after at least 130 hours of exposure to salt spray. The water-based polymer composition can also provide coatings with good initial water resistance, as measured according to the test method described in the Examples section below.
[0005] In a first aspect, the present invention provides a method for producing a composition comprising the steps of: (A) an emulsion polymer, comprising, based on weight of the emulsion polymer: 5% by weight to 28% by weight of cycloalkyl(meth)acrylate structural units; 0.1% to 10% by weight of acetoacetoxy or acetoacetamido functional monomeric structural units; 0.05% to 10% by weight of structural units of phosphorous acid monomers, their salts, or mixtures thereof; 0-10% by weight of an additional ethylenically unsaturated acid monomer, and an emulsion polymer comprising structural units of an additional ethylenically unsaturated nonionic monomer; and (B) a water-based resin comprising 0.7% to 7.8% by dry weight, based on the total dry weight of the emulsion polymer and the water-based resin, of at least one fatty acid ester segment and having a number average molecular weight of 20,000 grams per mole (g / mol) or less.
[0006] In a second aspect, the invention is a method of preparing the aqueous polymer composition of the first aspect by mixing an emulsion polymer with a water-based resin.
[0007] In a third aspect, the invention is a coating composition comprising the aqueous polymeric composition of the first aspect and, optionally, a pigment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] An "aqueous" composition or dispersion herein means that the particles are dispersed in an aqueous medium. By "aqueous medium" herein is meant water and 0-30% by weight, based on the weight of the medium, of a water-miscible compound(s), such as, for example, an alcohol, a glycol, a glycol ether, a glycol ester, or a mixture thereof.
[0009] A "structural unit," also known as a "polymerized unit" of a specified monomer, refers to the remnant of the monomer after polymerization, i.e., the polymerized monomer or the polymerized form of the monomer. For example, the structural unit of methyl methacrylate is shown below:
[0010] [ka] where the dotted lines represent the points of attachment of the structural units to the polymer backbone.
[0011] In the present specification, the term "fatty acid ester segment" refers to (i) a remnant of a fatty acid after esterification or (ii) a remnant of an unsaturated fatty acid ester after polymerization, i.e., a structural unit of an unsaturated fatty acid ester. For example, a fatty acid ester segment derived from an eleostearic acid dimer after esterification and a fatty acid ester segment derived from a sulfated castor oil after polymerization (i.e., a structural unit of a sulfated castor oil) are shown as (i-1) and (ii-1), respectively:
[0012] [ka] (where the dotted lines represent the attachment points of the segments to the resin backbone).
[0013] As used herein, "acrylic" monomers include (meth)acrylic acid, alkyl (meth)acrylates, (meth)acrylamides, (meth)acrylonitrile, and modified forms thereof, such as hydroxy (meth)alkyl acrylates. Throughout this document, the fragment "(meth)acrylic" refers to both "methacrylic" and "acrylic." For example, (meth)acrylic acid refers to both methacrylic acid and acrylic acid, and methyl (meth)acrylate refers to both methyl methacrylate and methyl acrylate.
[0014] As used herein, "glass transition temperature" or "T g " can be measured by a variety of techniques, including, for example, differential scanning calorimetry ("DSC") or calculation using the Fox equation. Specific values of Tg reported herein are calculated using the Fox equation (TG Fox, Bull. Am. Physics Soc., Volume 1, Issue No. 3, page 123 (1956)). For example, the Tg of a copolymer of monomers M1 and M2 is g For the calculation of
[0015]
number
[0016] The aqueous polymer composition of the present invention comprises one or more emulsion polymers. The emulsion polymers useful in the present invention comprise one or more cycloalkyl(meth)acrylate structural units. Examples of suitable cycloalkyl(meth)acrylates include cyclohexyl(meth)acrylate, metacyclohexyl(meth)acrylate, isobornyl(meth)acrylate, dihydrodicyclopentadienyl(meth)acrylate, trimethylcyclohexyl(meth)acrylate, t-butyl(meth)cyclohexylacrylate, or mixtures thereof. Preferred cycloalkyl(meth)acrylates include cyclohexyl methacrylate, cyclohexyl acrylate, metacyclohexyl acrylate, or mixtures thereof. The emulsion polymer may comprise cycloalkyl (meth)acrylate structural units in an amount of 5% by weight or more, 6% by weight or more, 7% by weight or more, 8% by weight or more, 9% by weight or more, 10% by weight or more, 11% by weight or more, 12% by weight or more, 13% by weight or more, 14% by weight or more, or even 15% by weight or more, and at the same time 28% by weight or less, 27% by weight or less, 26% by weight or less, 25% by weight or less, 24% by weight or less, 23% by weight or less, 22% by weight or less, 21% by weight or less, or even 20% by weight or less, based on the weight of the emulsion polymer. In this specification, the "weight of the emulsion polymer" refers to the dry weight of the emulsion polymer.
[0017] The emulsion polymers useful in the present invention may also contain structural units of one or more acetoacetoxy or acetoacetamido functional monomers. Acetoacetoxy or acetoacetamido functional monomers are ethylenically unsaturated and
[0018] [ka] (In the formula, R 1 is a monomer having one or more acetoacetyl moieties represented by the formula:
[0019] Examples of suitable acetoacetoxy or acetoacetamido functional groups include:
[0020] [ka] where X is O or N, R1 is a divalent radical, and R2 is a trivalent radical, which attach acetoacetoxy or acetoacetamido functionality to the backbone of the emulsion polymer.
[0021] Suitable acetoacetoxy or acetoacetamido functional monomers can include, for example, acetoacetoxyalkyl (meth)acrylates, such as acetoacetoxyethyl methacrylate (AAEM), acetoacetoxyethyl acrylate, acetoacetoxypropyl methacrylate, acetoacetoxybutyl methacrylate, and 2,3-di(acetoacetoxy)propyl methacrylate; allyl acetoacetate; vinyl acetoacetate; acetoacetamidoalkyl (meth)acrylates, such as acetoacetamidoethyl methacrylate and acetoacetamidoethyl acrylate; or combinations thereof. The emulsion polymer may comprise structural units of acetoacetoxy or acetoacetamido functional monomers in an amount of 0.1 wt% or more, 0.3 wt% or more, 0.5 wt% or more, 0.8 wt% or more, 1 wt% or more, 1.2 wt% or more, 1.5 wt% or more, 1.8 wt% or more, 2 wt% or more, 2.2 wt% or more, 2.5 wt% or more, 2.8 wt% or more, 3 wt% or more, or even 3.2 wt% or more, while at most 10 wt%, 9 wt% or less, 8 wt% or less, 7 wt% or less, 6 wt% or less, 5 wt% or less, 4.5 wt% or less, 4 wt% or less, 3.8 wt% or less, 3.6 wt% or less, or even 3.4 wt% or less, based on the weight of the emulsion polymer.
[0022] The emulsion polymers useful in the present invention may contain structural units of one or more phosphorous acid monomers, their salts, or mixtures thereof. The phosphorous acid monomer may have ethylenic unsaturation. The phosphorous acid monomer may be a dihydrogen phosphate ester of an alcohol, where the alcohol contains or is substituted with a polymerizable vinyl or olefinic group. The phosphorous acid monomers and their salts include phosphoalkyl(meth)acrylates, such as phosphoethyl(meth)acrylate, phosphopropyl(meth)acrylate, phosphobutyl(meth)acrylate, salts thereof, and mixtures thereof; CH2=C(R p1 )-C(O)-O-(R p2 O) q -P(O)(OH)2 (wherein, R p1 =H or CH3, R p2= alkylene, such as an ethylene group, a propylene group, or a combination thereof, q=1-20), such as SIPOMER PAM-100, SIPOMER PAM-200, SIPOMER PAM-300, and SIPOMER PAM-600, all of which are available from Solvay; phosphoalkoxy (meth)acrylates, such as phosphoethylene glycol (meth)acrylate, phosphodiethylene glycol (meth)acrylate, phosphotriethylene glycol (meth)acrylate, phosphopropylene glycol (meth)acrylate, phosphodipropylene glycol (meth)acrylate, phosphotripropylene glycol (meth)acrylate, salts thereof, and mixtures thereof. Preferred phosphorous acid monomers are selected from the group consisting of phosphoethyl methacrylate (PEM), phosphoethyl acrylate, allyl ether phosphate, or mixtures thereof, and more preferably phosphoethyl methacrylate. The emulsion polymer may comprise structural units of a phosphorous acid monomer, a salt thereof, or mixtures thereof in an amount of 0.05 wt.% or more, 0.1 wt.% or more, 0.2 wt.% or more, 0.3 wt.% or more, 0.5 wt.% or more, 0.6 wt.% or more, 0.8 wt.% or more, 1.0 wt.% or more, 1.2 wt.% or more, 1.3 wt.% or more, 1.4 wt.% or more, or even 1.5 wt.% or more, while at most 10 wt.%, 7 wt.% or less, 5 wt.% or less, 4.5 wt.% or less, 4 wt.% or less, 3.5 wt.% or less, 3.2 wt.% or less, 3 wt.% or less, 2.8 wt.% or less, 2.5 wt.% or less, 2 wt.% or less, or even 1.8 wt.% or less, based on the weight of the emulsion polymer.
[0023] The emulsion polymers useful in the present invention may contain structural units of one or more additional ethylenically unsaturated acid monomers, their salts, or mixtures thereof, other than the phosphorous acid monomers or their salts. The additional ethylenically unsaturated acid monomers may be carboxylic acid monomers, sulfonic acid monomers, or mixtures thereof. Carboxylic acid monomers may include α,β-ethylenically unsaturated carboxylic acids, monomers having acid-forming groups that generate or can be subsequently converted into such acid groups (e.g., anhydrides, (meth)acrylic anhydride, or maleic anhydride), and mixtures thereof. Specific examples of α,β-ethylenically unsaturated carboxylic acid monomers include acrylic acid, methacrylic acid, maleic acid, itaconic acid, crotonic acid, fumaric acid, 2-carboxyethyl acrylate, or mixtures thereof. Sulfonic acid monomers may include sodium vinyl sulfonate (SVS), sodium styrene sulfonate (SSS), and acrylamido-methyl-propane sulfonate (AMPS), their salts, or mixtures thereof. Preferably, the additional ethylenically unsaturated acid monomer is an α,β-ethylenically unsaturated carboxylic acid, such as acrylic acid, methacrylic acid, itaconic acid, or a mixture thereof. The emulsion polymer may contain structural units of additional acid monomers and their salts in an amount of 0 or more, 0.5% or more, 0.8% or more, 1% or more, 1.2% or more, 1.5% or more, 1.8% or more, or even 2% or more by weight, based on the weight of the emulsion polymer, and at the same time 10% or less, 7% or less, 5% or less, 4.5% or less, 4% or less, 3.5% or less, 3% or less, or even 2.5% or less by weight.
[0024] Emulsion polymers useful in the present invention may also contain structural units of one or more ethylenically unsaturated functional monomers other than those monomers mentioned above having one or more functional groups selected from ureido, amide, amino, silane, hydroxyl, or combinations thereof. These ethylenically unsaturated functional monomers can include amino functional monomers such as dimethylaminoethyl methacrylate, dimethylaminoethyl acrylate, dimethylaminopropyl methacrylate, dimethylaminopropyl acrylate; monomers with amide functionality such as acrylamide and methacrylamide; vinyl trialkoxysilanes such as vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(2-methoxyethoxy)silane, vinyldimethylethoxysilane, vinylmethyldiethoxysilane, or (meth)acryloxyalkyl trialkoxysilanes such as (meth)acryloxyethyltrimethoxysilane and (meth)acryloxypropyltrimethoxysilane; ureido functional monomers; hydroxyl functional monomers such as 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, and 3-hydroxybutyl methacrylate; or mixtures thereof.Preferably, the ethylenically unsaturated functional monomer is a ureido functional monomer. As used herein, the term "ureido-functional monomer" refers to an ethylenically unsaturated compound that contains a cyclic ureido group (i.e., an imidazolidin-2-one group). The ureido-functional monomer may include a cyclic ureido-group-containing alkyl ester of (meth)acrylic acid. Examples of suitable ureido-functional monomers include N-(2-methacrylamidoethyl)ethyleneurea, N-(2-methacryloyloxyethyl)ethyleneurea, N-(maleatediethyl)ethyleneurea, or mixtures thereof. A preferred ureido-functional monomer is N-(2-methacryloyloxyethyl)ethyleneurea.The emulsion polymer may comprise structural units of ethylenically unsaturated functional monomers in an amount of 0 or more, 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, 0.6 or more, or even 0.7 or more, and at the same time 3 or less, 2.5 or less, 2 or less, 1.5 or less, 1.1 or less, 1 or less, 0.9 or less, or even 0.8 or less, based on the weight of the emulsion polymer.
[0025] The emulsion polymers useful in the present invention may contain structural units of one or more additional ethylenically unsaturated nonionic monomers other than cycloalkyl (meth)acrylate, acetoacetoxy or acetoacetamide functional monomers, and ethylenically functional monomers. In this specification, "nonionic monomer" refers to a monomer that does not have an ionic charge at pH=1-14. Ethylenically unsaturated nonionic monomers include C1-C 24 Alkyl (meth)acrylates, for example, C4-C 24 Examples of the alkyl (meth)acrylate include alkyl (meth)acrylate, styrene, substituted styrene, (meth)acrylonitrile, and mixtures thereof. 24 Alkyl (meth)acrylate refers to an alkyl ester of (meth)acrylic acid containing an alkyl having 1 to 24 carbon atoms. Examples of suitable additional ethylenically unsaturated nonionic monomers include methyl methacrylate, ethyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, butyl (meth)acrylate, tert-butyl (meth)acrylate, lauryl (meth)acrylate, or mixtures thereof. Additional ethylenically unsaturated nonionic monomers include styrene, substituted styrene, C4-C 24The emulsion polymer may comprise any one or any combination of more than one ethylenically unsaturated nonionic monomer selected from alkyl (meth)acrylates, alkyl (meth)acrylates, or mixtures thereof. The emulsion polymer may comprise structural units of additional ethylenically unsaturated nonionic monomers in an amount of 42% by weight or more, 45% by weight or more, 50% by weight or more, 55% by weight or more, or even 60% by weight or more, and at the same time 94% by weight or less, 90% by weight or less, 85% by weight or less, 80% by weight or less, 75% by weight or less, 70% by weight or less, or even 65% by weight or less, based on the weight of the emulsion polymer.
[0026] The emulsion polymers useful in the present invention may contain one or more structural units of a polymerizable surfactant. The polymerizable surfactant may contain at least one carbon-carbon double bond. The polymerizable surfactant may have the structure of formula (I):
[0027] [ka] (wherein R1 is a phenyl group or
[0028] [ka] wherein R is an alkylene group, m1 is an integer from 0 to 4, for example, 0, 1, 2, 3, or 4, preferably 1 to 3, R2 is an alkyl or substituted alkyl, preferably, C1 to C4 alkyl or substituted C1 to C4 alkyl, m2 is 0 or 1, and R3 is hydrogen or a C1 to C4 alkyl such as methyl. 20 or a C1-C4 alkyl group, and R4 is hydrogen or a C1-C 20 or a C1-C4 alkyl group, A represents an alkylene group or a substituted alkylene group having 2 to 4 carbon atoms, n represents the average number of moles of alkylene oxide added and is an integer ranging from 0 to 1,000, 1 to 100, 2 to 60, 3 to 50, or 4 to 40, and X is hydrogen or -(CH2) a -SO3M, -(CH2) brepresents an anionic hydrophilic group selected from -COOM, -PO3M2, -P(Z)OM, or -CO-CH2-CH(SO3M)-COOM (wherein a and b are each independently an integer of 0 to 4), Z represents a residue obtained by removing X from general formula (I), and each M represents hydrogen, an alkali metal atom, an alkaline earth metal atom, an ammonium residue, or an alkanolamine residue).
[0029] In formula (I), R1 is
[0030] [ka] (wherein R may be an alkylene group having 1 to 4 carbon atoms, preferably having 2 to 3 carbon atoms, such as -CH2-, -CH(CH3)-, or -C(CH3)2-). Preferred R1 is
[0031] [ka] Preferably, m1 is 2 or 3. In formula (I), A may be an ethylene group (-CH2CH2-), and n may be an integer ranging from 4 to 40 or 5 to 20. Preferred X is -SO3M. Preferably, M is NH4 + Specific examples of polymerizable surfactants include those having the following structure:
[0032] [ka] (wherein m1 and n are as defined above in formula (I), and M is Li + , Na + , K + , or NH4 +(wherein: HITENOL AR-1025 manufactured by DKS Co., Ltd.) Suitable commercially available polymerizable surfactants include Hitenol AR-1025 manufactured by DKS Co., Ltd. The emulsion polymer useful in the present invention may contain structural units of polymerizable surfactant in an amount of 0 or more, 0.5 or more, 0.7 or more, 0.9 or more, 1.1 or more, or even 1.2 or more by weight based on the weight of the emulsion polymer, while 10 or less, 7 or less, 5 or less, 3 or less, 2 or less, 1.5 or less, or even 1.3 or less by weight.
[0033] The emulsion polymers useful in the present invention may optionally contain structural units of one or more polyfunctional ethylenically unsaturated monomers, including di-, tri-, tetra- or higher functional ethylenically unsaturated monomers other than those mentioned above. Examples of suitable multi-ethylenically unsaturated monomers include butadiene, allyl (meth)acrylate, divinylbenzene, ethylene glycol dimethacrylate, butylene glycol dimethacrylate, or mixtures thereof. The emulsion polymer may contain 0 to 5% by weight, for example, 3% or less, 2% or less, 1% or less, 0.5% or less, 0.1% or less, or even 0, of polyfunctional ethylenically unsaturated monomers, based on the weight of the emulsion polymer.
[0034] The emulsion polymers useful in the present invention may contain, based on the weight of the emulsion polymer, 10% to 25% by weight of structural units of a cycloalkyl (meth)acrylate, 1.5% to 4% by weight of structural units of an acetoacetoxy or acetoacetamide functional monomer, 1.5% to 4% by weight of structural units of a phosphorous acid monomer, its salt, or mixtures thereof, additional ethylenically unsaturated nonionic monomer, and optionally 0 to 3% by weight of structural units of an ethylenically unsaturated functional monomer.
[0035] The total weight concentration of structural units in the emulsion polymer is equal to 100%. The types and levels of the above monomers for preparing the emulsion polymer can be selected to provide the emulsion polymer with a glass transition temperature (Tg) suitable for various applications. g may be equal to or greater than 0° C., equal to or greater than 5° C., equal to or greater than 10° C., equal to or greater than 15° C., equal to or greater than 20° C., equal to or greater than 25° C., or even equal to or greater than 30° C., and at the same time equal to or less than 60° C., equal to or less than 55° C., equal to or less than 50° C., equal to or less than 47° C., equal to or less than 44° C., or even equal to or less than 40° C., as calculated by the Fox equation.
[0036] The emulsion polymers useful in the present invention can have a molecular weight of 10,000 g / mol or more, e.g., 15,000 g / mol or more, 20,000 g / mol or more, 25,000 g / mol or more, 30,000 g / mol or more, 35,000 g / mol or more, 40,000 g / mol or more, 45,000 g / mol or more, 50,000 g / mol or more, or even 55,000 g / mol or more, while having a molecular weight of 1,000,000 g / mol or less, 800,000 g / mol or less, or a mixture thereof. The emulsion polymer may have a number average molecular weight (Mn) of up to 600,000 g / mol, up to 400,000 g / mol, up to 300,000 g / mol, up to 200,000 g / mol, up to 150,000 g / mol, up to 120,000 g / mol, up to 100,000 g / mol, up to 80,000 g / mol, up to 70,000 g / mol, up to 65,000 g / mol, or even up to 60,000 g / mol. The molecular weight of the emulsion polymer may be measured by gel permeation chromatography (GPC), as described in the Examples section below.
[0037] The emulsion polymers useful in the present invention may be prepared by emulsion polymerization of a mixture of the monomers described above ("monomer mixture"). The total concentration of the monomers in the monomer mixture for preparing the emulsion polymer is equal to 100%. For each monomer, the weight concentration of the monomer in the monomer mixture (i.e., based on the total weight of the monomer mixture) is the same as the above-mentioned weight concentration of the structural unit of such monomer in the emulsion polymer (i.e., based on the weight of the emulsion polymer). The monomer mixture may be added neat or as an emulsion in water, or in one or more additions, or continuously, linearly, or non-linearly over the reaction period to prepare the emulsion polymer. The monomer mixture may be added neat or as an emulsion in water, or in one or more additions, or continuously, linearly, or non-linearly over the reaction period to prepare the polymer. The temperature suitable for the free radical polymerization process may be less than 100°C, in the range of 10°C to 99°C, or in the range of 50°C to 90°C. One or more surfactants, preferably polymerizable surfactants, may be used in the preparation of the polymer.
[0038] The polymerization process may use one or more radical initiators. The polymerization process may be a thermally initiated or redox initiated emulsion polymerization. Examples of suitable free radical initiators include hydrogen peroxide, t-butyl hydroperoxide, cumene hydroperoxide, ammonium and / or alkali metal persulfate, sodium perborate, superphosphate and their salts; potassium permanganate, and ammonium or alkali metal salts of peroxydisulfate. Free radical initiators may typically be used at levels of 0.01% to 3.0% by weight, based on the total weight of monomers. The polymerization process may use a redox system comprising the above-mentioned initiators in combination with a suitable reducing agent. Examples of suitable reducing agents include sodium formaldehyde sulfoxylate, ascorbic acid, isoascorbic acid, alkali metal and ammonium salts of sulfur-containing acids, such as sodium sulfite, bisulfite, thiosulfate, hydrosulfite, sulfide, hydrogen sulfide, or dithionous acid, formazin sulfinic acid, acetone bisulfite, glycolic acid, hydroxymethanesulfonic acid, glyoxylic acid hydrate, lactic acid, glyceric acid, malic acid, tartaric acid, and salts of the aforementioned acids.Metal salts of iron, copper, manganese, silver, platinum, vanadium, nickel, chromium, palladium, or cobalt may be used to catalyze the redox reaction.Optionally, a chelating agent for the metal may be used.
[0039] One or more chain transfer agents may be used in the polymerization process to control the molecular weight of the emulsion polymer. Examples of suitable chain transfer agents include 3-mercaptopropionic acid, methyl 3-mercaptopropionate, butyl 3-mercaptopropionate, n-dodecyl mercaptan, n-hexadecanethiol, tert-dodecyl mercaptan, n-octadecanethiol, benzenethiol, alkyl mercaptan azelates, hydroxyl-containing mercaptans such as hydroxyethyl mercaptan, mercaptopropionic acid, and mixtures thereof. Chain transfer agents may be used in amounts of 0 to 2% by weight, for example, 1.5% by weight or less, 1% by weight or less, 0.5% by weight or less, 0.3% by weight or less, 0.2% by weight or less, or even 0.15% by weight or less, based on the total weight of the monomers (i.e., monomer mixture) used to prepare the emulsion polymer.
[0040] After polymerization is complete, the resulting aqueous dispersion can be neutralized with one or more bases as neutralizing agents, for example to a pH value of at least 5, 6 to 12, 7 to 10, or 8 to 9. The base can result in partial or complete neutralization of the ionic or potentially ionic groups of the emulsion polymer. Examples of suitable bases include ammonia; alkali metal or alkaline earth metal compounds such as sodium hydroxide, potassium hydroxide, calcium hydroxide, zinc oxide, magnesium oxide, sodium carbonate; primary, secondary, and tertiary amines such as triethylamine, ethylamine, propylamine, monoisopropylamine, monobutylamine, hexylamine, ethanolamine, diethylamine, dimethylamine, tributylamine, triethanolamine, dimethoxyethylamine, 2-ethoxyethylamine, 3-ethoxypropylamine, dimethylethanolamine, diisopropanolamine, morpholine, ethylenediamine, 2-diethylaminoethylamine, 2,3-diaminopropane, 1,2-propylenediamine, neopentanediamine, dimethylaminopropylamine, hexamethylenediamine, 4,9-dioxadodecane-1,12-diamine, polyethyleneimine, or polyvinylamine; aluminum hydroxide, or mixtures thereof. The emulsion polymer particles in the aqueous dispersion may have a particle size of 50 nanometers (nm) or more, 80 nm or more, or even 90 nm or more, and at the same time 500 nm or less, 200 nm or less, or even 150 nm or less. Particle size herein is referred to as Z-average size and can be measured by a Brookhaven BI-90 Plus Particle Size Analyzer.
[0041] The aqueous polymer composition of the present invention may comprise emulsion polymer in an amount of 92.2% by weight or more, 92.3% by weight or more, 92.4% by weight or more, 92.5% by weight or more, 92.6% by weight or more, 92.7% by weight or more, 92.8% by weight or more, 93% by weight or more, 93.2% by weight or more, 93.5% by weight or more, 93.8% by weight or more, 94% by weight or more, 94.2% by weight or more, 94.5% by weight or more, 94.8% by weight or more, or even 95% by weight or more, while at the same time 99.3% by weight or less, 99.2% by weight or less, 99.1% by weight or less, 99% by weight or less, 98.8% by weight or less, 98.5% by weight or less, 98.2% by weight or less, or even 98% by weight or less, based on the total dry weight of the emulsion polymer and the aqueous resin described below.
[0042] The water-based polymer composition of the present invention also includes one or more water-based resins that contain at least one fatty acid ester segment other than the emulsion polymer described above. In this specification, "water-based resin" refers to a resin that can be soluble or dispersible in water. The water-based resin useful in the present invention can be a water-based epoxy ester, an unsaturated fatty acid ester modified acrylic copolymer, or a mixture thereof.
[0043] The water-based epoxy ester useful in the present invention may contain one or more fatty acid ester segments. The fatty acid ester segment can be formed by reacting an epoxy compound with a fatty acid, preferably an unsaturated fatty acid. The water-based epoxy ester may include a reaction product of an epoxy compound with an unsaturated fatty acid, and optionally an additional carboxylic acid group-containing compound other than the unsaturated fatty acid. Typically, one or more solvents, such as butanol, dimethylbenzene, 2-butoxy-1-ethanol monobutyl ether, ethylene glycol monoethyl ether, or mixtures thereof, are used to dilute the reaction product. The epoxy group in the epoxy compound can react with the carboxylic acid group in the unsaturated fatty acid by a condensation reaction to form at least one unsaturated fatty acid ester segment (i.e., a remnant of the unsaturated fatty acid after esterification) in the water-based epoxy ester. The epoxy compound can be an aliphatic, aromatic, or cycloaliphatic epoxy compound, or a mixture thereof. Suitable epoxy compounds include, for example, diglycidyl ether of bisphenol A, diglycidyl ether of bisphenol F, diglycidyl ether of bialcohol, diglycidyl ether of polyglycol, diglycidyl ether of polypropylene glycol, or mixtures thereof. The unsaturated fatty acid may contain 6 to 36 carbon atoms, 6 to 30 carbon atoms, 8 to 24 carbon atoms, or 8 to 18 carbon atoms. Examples of suitable unsaturated fatty acids include soybean oil acid, lauric acid, cocinic acid, eleostearic acid, tung oil fatty acid, linseed oil fatty acid, dehydrated castor oil fatty acid, dimers or oligomers thereof, or mixtures thereof. When the unsaturated fatty acid used to prepare the water-based epoxy ester is a monocarboxylic acid, the resulting epoxy ester has the structure of formula (IIa): C na H ma O2- (IIa), (wherein na is an integer from 6 to 18, and ma=2na-3, 2na-5, or 2na-7).
[0044] When the unsaturated fatty acid used to prepare the water-based epoxy ester is an unsaturated fatty acid dimer, the resulting epoxy ester has the structure of formula (IIb): -O2C-C nb H mb -CO2- (IIb), (wherein nb is an integer from 10 to 36, and mb = 2nb-4, 2nb-6, 2nb-8, 2nb-10, or 2nb-12).
[0045] Additional carboxylic acid group-containing compounds useful for preparing epoxy esters can include ethylenically unsaturated carboxylic acid monomers, which can be mono- or dicarboxylic acids, polyacrylic acid, polyacrylates containing carboxylic acid groups, or mixtures thereof. Carboxylic acid monomers can include those described in the emulsion polymer section above, especially (meth)acrylic acid. Preferably, the epoxy ester is a (meth)acrylic acid functionalized epoxy ester. In the reaction to form the epoxy ester, the molar ratio of carboxylic acid groups to epoxy groups in the reactants can range from 10:1 to 1:1, 5:1 to 1:1, 2:1 to 1:1, 1.8:1 to 1:1, 1.5:1 to 1:1, or 1.2:1 to 1:1. The epoxy ester resin can be further modified with α,β-ethylenically unsaturated dicarboxylic acids and / or anhydrides thereof via addition reaction with the double bond(s) in the epoxy ester (i.e., forming carboxylic acid groups), and then further neutralized with ammonia and / or amines to a pH value of greater than 9 or 9.5 or greater. Suitable α,β-ethylenically unsaturated dicarboxylic acids can include, for example, maleic anhydride, fumaric acid, itaconic acid, or mixtures thereof. Suitable amines can include, for example, ethanolamine, triethanolamine, dimethylethanolamine, 1,6-diaminohexane, ethylenediamine, triethylethylenediamine, phenylenediamine, or mixtures thereof. The resulting water-based epoxy ester can include, for example, 5 wt.% or more, 10 wt.% or more, 15 wt.% or more, 17 wt.% or more, or even 19 wt.% or more, and at the same time 30 wt.% or less, 25 wt.% or less, or even 20 wt.% or less of the solvent typically used in the reaction for preparing the water-based epoxy ester, based on the wet weight of the water-based epoxy ester.
[0046] The water-based resin useful in the present invention may include an unsaturated fatty acid ester modified acrylic copolymer (hereinafter "modified acrylic copolymer"). Such copolymers may be prepared by polymerization of an unsaturated fatty acid ester with one or more acrylic monomers including acrylic acid, methacrylic acid, or mixtures thereof. The modified acrylic copolymer may include structural units of acrylic acid, methacrylic acid, or mixtures thereof in an amount of 20% by weight or more, 30% by weight or more, 40% by weight or more, 50% by weight or more, 60% by weight or more, or even 70% by weight or more, and at the same time 99% by weight or less, 95% by weight or less, 90% by weight or less, or even 85% by weight or less, based on the weight of the modified acrylic copolymer. As used herein, "unsaturated fatty acid ester" refers to an ester product of an unsaturated fatty acid and an alcohol. The alcohol may be any monohydric, dihydric, or polyhydric alcohol that can be condensed with an unsaturated fatty acid to form the corresponding unsaturated fatty acid ester. Typically, the alcohol contains at least one carbon atom. Typically, the alcohol contains less than 20 carbon atoms, less than 12 carbon atoms, or less than 8 carbon atoms. The carbon atoms may be arranged in a linear or branched configuration and may be substituted with various substituents, such as alkyl, cycloalkyl, monocyclic aromatic, arylalkyl, alkylaryl, hydroxyl, halogen, ether, ester, aldehyde, and keto substituents. Preferably, the alcohol is a linear or branched C1-C 12 The preferred alcohol is the trihydric alcohol glycerol, whose fatty acid esters are known as "glycerides". Other preferred alcohols include methanol and ethanol. Unsaturated fatty acid esters useful in the present invention can be obtained from oils such as linseed oil, tung oil, castor oil, dehydrated castor oil, soybean oil, tall oil, sunflower oil, and corn oil. Preferably, the unsaturated fatty acid esters are C8-C 25 Unsaturated fatty acid segments and C1-C 12It is derived from the alcohol segment. Suitable unsaturated fatty acid esters include monosaturated fatty acid esters formed from palmitoleic acid, oleic acid, or caproic acid; diunsaturated fatty acid esters formed from linoleic acid; triunsaturated fatty acid esters formed from linolenic acid or eleostearic acid, or mixtures thereof. Preferred fatty acid esters are cottonseed oil, castor oil, sulfated castor oil, soybean oil, coconut oil, olive oil, or mixtures thereof. The modified acrylic copolymer may contain structural units of unsaturated fatty acid esters in an amount of 1% to 50%, 3% to 45%, 6% to 40%, or 10% to 30% by weight based on the weight of the modified acrylic copolymer. Acrylic monomers useful for preparing the modified acrylic copolymer may also include one or more polyethylenically unsaturated monomers. The polyethylenically unsaturated monomers may include those described in the emulsion polymer section above, especially allyl methacrylate. The resulting modified acrylic copolymer may contain structural units of polyethylenically unsaturated monomers in an amount of 0-10%, 0.05%-5%, 0.1%-3%, or 0.15%-2% by weight based on the weight of the modified acrylic copolymer. The polymerization process for preparing the modified acrylic copolymer may be carried out as an emulsion polymerization as described in the Emulsion Polymer section above.
[0047] The aqueous resin useful in the present invention may have a number average molecular weight of 20,000 g / mol or less, for example, 19,000 g / mol or less, 18,000 g / mol or less, 17,000 g / mol or less, 16,000 g / mol or less, 15,000 g / mol or less, 14,000 g / mol or less, 13,000 g / mol or less, 12,000 g / mol or less, 11,000 g / mol or less, 10,000 g / mol or less, 9,000 g / mol or less, 8,000 g / mol or less, 7,000 g / mol or less, 6,000 g / mol or less, or even 5,000 g / mol or less. The molecular weight may be measured by GPC as described in the Examples section below.
[0048] The aqueous polymer composition of the present invention may comprise an amount of water-based resin of 0.7 dry weight% or more, 0.8 dry weight% or more, 0.9 dry weight% or more, 1.0 dry weight% or more, 1.2 dry weight% or more, 1.5 dry weight% or more, 1.8 dry weight% or more, or even 2 dry weight% or more, and at the same time 7.8 dry weight% or less, 7.7 dry weight% or less, 7.6 dry weight% or less, 7.5 dry weight% or less, 7.4 dry weight% or less, 7.3 dry weight% or less, 7.2 dry weight% or less, 7 dry weight% or less, 6.8 dry weight% or less, 6.5 dry weight% or less, 6.2 dry weight% or less, 6 dry weight% or less, 5.8 dry weight% or less, 5.5 dry weight% or less, 5.2 dry weight% or less, or even 5 dry weight% or less, based on the total dry weight of the emulsion polymer and the water-based resin.
[0049] The aqueous polymer composition of the present invention may contain ammonia and / or amine in an amount of 0.005% by weight or more, 0.01% by weight or more, 0.02% by weight or more, 0.03% by weight or more, or even 0.04% by weight or more, and at the same time 5% by weight or less, 4% by weight or less, 2% by weight or less, 1% by weight or less, 0.8% by weight or less, or even 0.7% by weight or less, based on the total dry weight of the emulsion polymer and the aqueous resin. The aqueous polymer composition further contains water in an amount of, for example, 30% by weight to 90% by weight, 40% by weight to 80% by weight, 50% by weight to 70% by weight, or 55% by weight to 60% by weight, based on the total weight of the aqueous polymer composition.
[0050] The waterborne polymer composition of the present invention may optionally include one or more desiccants. "Desiccants" herein refers to the reaction product of a metal hydroxide and a fatty acid. The desiccants can promote crosslinking of the waterborne epoxy ester. Suitable desiccants can include, for example, cobalt 2-ethylhexanoate, cobalt naphthenate, manganese naphthenate, or mixtures thereof. The waterborne polymer composition can include an amount of desiccants of 15% or less, 12% or less, 10% or less, 9% or less, 8% or less, 7% or less, 5% or less, or even zero, based on the dry weight of the waterborne epoxy ester. Preferably, the waterborne polymer composition is substantially free of desiccants, for example, less than 4% or less, 3% or less, 2% or less, 1% or less, 0.5% or even zero, based on the dry weight of the waterborne epoxy ester.
[0051] The present invention also relates to a method for preparing an aqueous polymer composition by mixing an emulsion polymer, typically in an aqueous dispersion, with a water-based resin. By simply blending the emulsion polymer with the water-based resin ding, the method can provide easy processability and application.
[0052] The aqueous polymer composition of the present invention is particularly useful as a binder in coating applications. The present invention also relates to a coating composition comprising the aqueous polymer composition and optionally one or more pigments. The coating composition may comprise the aqueous polymer composition in an amount of 5% to 95%, 10% to 80%, or 20% to 70% by weight based on the total weight of the coating composition. As used herein, "pigment" refers to a material that can materially contribute to the opacity or hiding ability of the coating composition. Such materials typically have a refractive index greater than 1.8. Inorganic pigments typically include metal oxides. Examples of suitable pigments include titanium dioxide (TiO2), carbon black, iron oxide, zinc sulfide, lemon chrome yellow, black iron oxide, or mixtures thereof. Organic pigments typically include Prussian blue, organic pigment yellow, organic pigment red; anticorrosive pigments such as zinc phosphate, zinc molybdate, zinc oxide, aluminum tripolyphosphate, zinc phosphate molybdate, or modified zinc phosphate; or mixtures thereof. Carbon black may include acetylene black, channel black, furnace black, lamp black, and thermal black. Preferred pigments are carbon black, barium sulfate, zinc phosphate, or modified zinc phosphate, or mixtures thereof. More preferably, the pigment is carbon black.
[0053] The coating composition of the present invention may include one or more extenders. "Extender" herein refers to a particulate inorganic material having a refractive index of 1.8 or less and greater than 1.3. Examples of suitable extenders include barium sulfate, talc, calcium carbonate, clay, calcium sulfate, aluminum silicate, silicates, zeolites, mica, diatomaceous earth, solid or hollow glass, ceramic beads, nepheline syenite, feldspar, diatomaceous earth, calcined diatomaceous earth, talc (hydrated magnesium silicate), silica, alumina, kaolin, pyrophyllite, perlite, barite, wollastonite, opaque polymers such as ROPAQUE™ Ultra E available from The Dow Chemical Company (ROPAQUE is a trademark of The Dow Chemical Company), or mixtures thereof. The coating composition may have a pigment volume concentration (PVC) of 0-55%, 5-40%, or 10-35%. PVC is determined by the formula: PVC=[volume (顔料+増量剤) / Dry Volume (コーティング組成物) ] x 100%.
[0054] The coating composition of the present invention may include one or more defoamers. As used herein, "defoamer" refers to a chemical additive that reduces and prevents foam formation. The defoamer may be a silicone-based defoamer, a mineral oil-based defoamer, an ethylene oxide / propylene oxide-based defoamer, an alkyl polyacrylate, and mixtures thereof. Suitable commercially available defoamers include, for example, TEGO Airex 901 W, TEGO Airex 902 W, and TEGO Foamex 1488 polyether siloxane copolymer emulsions available from TEGO, BYK-022 and BYK-024 silicone defoamers available from BYK, and mixtures thereof. The defoamer may be present in an amount generally between 0 and 5 wt%, between 0.05 and 3 wt%, or between 0.1 and 2 wt%, based on the total weight of the coating composition.
[0055] The coating composition of the present invention may include one or more thickeners, also known as "rheology modifiers". Thickeners may include polyvinyl alcohol (PVA), clay materials, acid derivatives, acid copolymers, urethane associative thickeners (UAT), polyether urea polyurethanes (PEUPU), polyether polyurethanes (PEPU), or mixtures thereof. Examples of suitable thickeners include alkali swellable emulsions (ASE), such as sodium or ammonium neutralized acrylic acid polymers; hydrophobically modified alkali swellable emulsions (HASE), such as hydrophobically modified acrylic acid copolymers; associative thickeners, such as hydrophobically modified ethoxylated urethanes (HEUR); and cellulosic thickeners, such as methylcellulose ethers, hydroxymethylcellulose (HMC), hydroxyethylcellulose (HEC), hydrophobically modified hydroxyethylcellulose (HMHEC), sodium carboxymethylcellulose (SCMC), sodium carboxymethyl 2-hydroxyethylcellulose, 2-hydroxypropylmethylcellulose, 2-hydroxyethylmethylcellulose, 2-hydroxybutylmethylcellulose, 2-hydroxyethylethylcellulose, and 2-hydroxypropylcellulose. Preferably, the thickener is HEUR. The thickener may be present in an amount of 0 to 5 wt%, 0.05 wt% to 3 wt%, or 0.1 wt% to 1 wt%, based on the total weight of the coating composition.
[0056] The coating composition of the present invention may include one or more wetting agents. As used herein, "wetting agent" refers to a chemical additive that reduces the surface tension of the composition, making it easier for the composition to spread or penetrate the surface of a substrate. Wetting agents may be polycarboxylate, anionic, zwitterionic, or nonionic. Suitable commercially available wetting agents may include, for example, SURFYNOL 104 and SURFYNOL TG nonionic wetting agents based on acetylenic diols available from Evonik, BYK-190, TEGO-750W, and TEGO-755W solutions of high molecular weight block polymers with pigment-affinic groups available from BYK and Evonik, respectively, BYK-346 and BYK-349 polyether modified siloxanes, both available from BYK, or mixtures thereof. Wetting agents may be present at 0-5 wt%, 0.05 wt%-3 wt%, or 0.1 wt%-2 wt%, based on the total weight of the coating composition.
[0057] The coating composition of the present invention may include one or more coalescent agents. As used herein, "coalescent agent" refers to a slow-evaporating solvent that fuses polymer particles into a continuous film under ambient conditions. Examples of suitable coalescent agents include 2-n-butoxyethanol, dipropylene glycol n-butyl ether, propylene glycol n-butyl ether, dipropylene glycol methyl ether, propylene glycol methyl ether, propylene glycol n-propyl ether, diethylene glycol monobutyl ether, ethylene glycol monobutyl ether, ethylene glycol monohexyl ether, triethylene glycol monobutyl ether, dipropylene glycol n-propyl ether, n-butyl ether, or mixtures thereof. Preferred coalescent agents include dipropylene glycol n-butyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, n-butyl ether, or mixtures thereof. The coalescent agent may be present at 0 to 15 wt%, 0.5 to 8 wt%, or 2 to 5 wt%, based on the total weight of the coating composition.
[0058] The coating composition of the present invention may include one or more dispersants. The dispersants may be polyacrylic or polymethacrylic acids or maleic anhydrides with various monomers such as styrene, acrylate or methacrylate esters, diisobutylene, and other hydrophilic or hydrophobic comonomers; salts thereof; or mixtures thereof. The dispersants may be present in an amount of 0-5 wt%, 0.05 wt%-3 wt%, or 0.1 wt%-1 wt%, based on the total weight of the coating composition.
[0059] In addition to the above-mentioned components, the coating composition of the present invention may include any one or combination of the following additives: buffering agents, neutralizing agents, humectants, mildewcides, biocides, antiskinning agents, colorants, flow agents, antioxidants, plasticizers, leveling agents, adhesion promoters, flash rust prevention additives, and grinding media. These additives may be present in a combined amount of 0-10% or 0.1%-2% by weight based on the total weight of the coating composition. The coating composition may also include water in an amount of 30%-90%, 40%-80%, or 50%-70% by weight of the coating composition.
[0060] The coating composition of the present invention can be prepared by mixing the aqueous polymer composition with the pigment and, optionally, other ingredients as described above. The components in the coating composition can be mixed in any order to provide the coating composition of the present invention. Also, any of the optional ingredients described above can be added to the coating composition during or before mixing to form the coating composition. The pigment and / or extender are preferably mixed with a dispersant to form a slurry of the pigment and / or extender.
[0061] The coating composition of the present invention can be applied to and adhered to a variety of substrates. Examples of suitable substrates include wood, metal, plastic, foam, stone, elastomeric substrates, glass, fabric, concrete, or cement-based substrates. The coating composition is suitable for a variety of applications, such as marine protective coatings, general industrial finishes, metal protective coatings, automotive coatings, traffic paints, exterior insulation finish systems (EIFS), wood coatings, coil coatings, plastic coatings, can coatings, architectural coatings, and civil engineering coatings. The coating composition is particularly suitable for metal protective coatings. The coating composition may be used as a primer, a topcoat, a one-coat direct-to-metal coating, or may be used in combination with other coatings to form multi-layer coatings.
[0062] The coating composition of the present invention can be applied to a substrate by conventional means including brushing, dipping, rolling, and spraying. Aqueous compositions are preferably applied by spraying. Standard spraying techniques and equipment for spraying, such as air atomized spraying, air spraying, airless spraying, high volume low pressure spraying, and electrostatic spraying, such as electrostatic bell application, and either manual or automatic methods can be used. After the coating composition of the present invention is applied to a substrate, the coating composition can be dried at a temperature ranging from 0 to 35°C, or at elevated temperatures, such as 35°C to 240°C, to form a film (i.e., coating).
[0063] The coating composition of the present invention can impart improved corrosion resistance to coatings made therefrom. The present invention also provides a method for improving the corrosion resistance of a substrate susceptible to corrosion, such as a metal. The method includes providing a substrate susceptible to corrosion, applying a coating composition to the substrate susceptible to corrosion (i.e., coating the coating composition on the substrate susceptible to corrosion), and drying the coating composition to form a coated substrate. The corrosion resistance is characterized by a maximum creep at scribe of 2 mm, preferably 1.7 mm or less, 1.5 mm or less, 1.2 mm or less, or even 1 mm or less, at a dry film thickness of 40 to 60 micrometers (μm) after at least 130 hours of exposure to salt spray. The coating composition of the present invention can also provide a coating having good initial water resistance, as indicated by a blister rating of 10, 8F, or 6F and a rust rating of 10, 9P, 9S, or 9G. The corrosion resistance and initial water resistance properties can be measured according to the test methods described in the Examples section below. The present invention also relates to articles made by the method. The present invention also relates to a process for preparing the coating, which may include applying a coating composition to a substrate and drying the applied coating composition to form a coating having the properties defined above.
[0064] The coating compositions of the present invention, which include an aqueous polymeric composition as a binder, dry faster than conventional epoxy ester coating compositions (which typically include an epoxy ester as the only binder), allowing for higher production efficiencies. For example, when the coating composition is applied to a substrate and allowed to dry for 1-6 hours, such as 2 hours or less, the two resulting coated surfaces can be stacked or placed in contact with one another without damaging the coating when separating the two coated surfaces. In contrast, conventional epoxy ester coating compositions require at least 24 hours of drying before the coated surfaces can be stacked. EXAMPLES
[0065] Some embodiments of the present invention are now described in the following examples, in which all parts and percentages are by weight unless otherwise indicated.
[0066] Cyclohexyl methacrylate (CHMA) is available from BASF.
[0067] Styrene (ST) is available from Langyuan Chemical Co., Ltd.
[0068] Sulfated castor oil is available from Hydrior AG.
[0069] 2-Ethylhexyl acrylate (2-EHA) is available from The Dow Chemical Company.
[0070] Methacrylic acid (MAA), acrylic acid (AA), allyl methacrylate (ALMA), isoascorbic acid (IAA), n-dodecyl mercaptan (n-DDM), and NaNO2 flash rust prevention additives are available from Sinopharm Chemical Reagent Co., Ltd.
[0071] Phosphoethyl methacrylate (PEM) is available from Solvay.
[0072] N-(2-methacryloyloxyethyl)ethyleneurea (MEUR) is available from Evonik.
[0073] Acetoacetoxyethyl methacrylate (AAEM) is available from Eastman.
[0074] DISPERBYK-190 dispersant and DISPERBYK-022 defoamer are available from BYK.
[0075] Printex 4 carbon black, used as a pigment, is available from Orion.
[0076] BS-115 BaSO4 filler is available from GuangFu Jiancai.
[0077] OROTAN™ 731A dispersant, available from The Dow Chemical Company, is a hydrophobic polycarboxylic acid copolymer.
[0078] TEGO Airex 901w defoamer and TEGO Twin 4100 siloxane-based Gemini surfactant, used as a wetting agent, are both available from Evonik.
[0079] AMP 95 2-amino-2-methyl-1-propanol available from Angus is used as the neutralizing agent.
[0080] Texanol ester alcohol (3-hydroxy-2,2,4-trimethylpentyl isobutyrate), available from Eastman, is used as a coalescent.
[0081] ACRYSOL™ RM-8W nonionic urethane rheology modifier is available from The Dow Chemical Company.
[0082] YG-EA670 epoxy ester resin (solid content: 70%-75%) available from YangGuang HuiDe (China) is a water-based epoxy ester resin (M n :1,954g / mol).
[0083] RETAN™ 540 sulfated castor oil modified acrylic latex (solids content: 40%) (Mn: 4,687 g / mol) is available from The Dow Chemical Company.
[0084] OROTAN, RETAN, and ACRYSOL are trademarks of The Dow Chemical Company.
[0085] In determining the properties and characteristics described in the examples and herein, the following standard analytical equipment and methods are used.
[0086] solids content The solids content of the aqueous dispersion or water-based resin was measured by weighing 0.7±0.1 g of sample (the wet weight of the sample is denoted as "W1"), placing the sample in an aluminum pan (the weight of the aluminum pan is denoted as "W2") in an oven at 150°C for 25 minutes (min), then cooling to room temperature (20-25°C), weighing the aluminum pan with the dry sample, and denoting the total weight as "W3". "W3-W2" refers to the dry weight or solids weight of the sample. The solids content is calculated by (W3-W2) / W1×100%.
[0087] Salt spray resistance test The test coating composition was applied on the Q panel by using a 150 μm applicator. The resulting coated panel was first dried at 60° C. for 20 minutes and then dried at room temperature and 50% relative humidity (RH) for 7 days. A razor blade was used to make a scribe mark in the shape of an “X” by cutting the dry film on the coated panel. The as-prepared coated panels were then placed in a salt spray chamber by exposing them to a salt spray environment (5% sodium chloride fog) according to ASTM B117 (2011). After 130 hours of salt spray, the panels were removed from the salt spray chamber and washed with deionized (DI) water. The blister and rust creep along the scribe mark was then measured. The creep is the width of the maximum blister or rust starting from either side of the scribe mark. The criterion for passing the test is a maximum creep of 2 mm after 130 hours of salt spray testing.
[0088] Initial water resistance Coated panels were prepared by applying the test coating composition onto a Q panel (cold rolled steel) with a 150 μm applicator, then drying the coating composition for 2 hours at room temperature and 50% RH. The resulting coated panels were immersed in DI water at room temperature for 7 days. The degree of rust and blister on the coated panels was then evaluated and recorded according to ASTM D610 (2001) and ASTM D714-02 (2010), respectively. Panels with blister ratings of 10, 8F, or 6F and rust ratings of 10, 9P, 9S, or 9G are acceptable.
[0089] GPC analysis of water-based epoxy esters and emulsion polymers GPC analysis was typically performed by an Agilent 1200. Samples were dissolved in tetrahydrofuran (THF) / formic acid (FA) (5%) at a concentration of 2 mg / mL, shaken for 1 hour, stored at room temperature overnight, and then filtered through a 0.45 μm polytetrafluoroethylene (PTFE) filter prior to GPC analysis. GPC analysis was performed using the following conditions:
[0090] Columns: one PLgel GUARD column (10 μm, 50 mm x 7.5 mm), two Mixed B columns (7.5 mm x 300 mm) in series; column temperature: 40 °C; mobile phase: THF / FA (5%); flow rate: 1.0 mL / min; injection volume: 100 μL; detector: Agilent Refractive Index detector, 40 °C; and calibration curve: PL polystyrene narrow standards with molecular weights ranging from 2,329,000 to 580 g / mol using polynom 3 fitting.
[0091] GPC analysis of unsaturated fatty acid ester modified acrylic copolymer GPC analysis was typically performed by an Agilent 1200. Samples were dissolved in dimethylformamide (DMF) / FA (2%) at a concentration of approximately 2 mg / mL, stored at room temperature overnight, and then filtered through a 0.45 μm PTFE filter prior to GPC analysis. GPC analysis was performed using the following conditions:
[0092] Columns: one PSS GUARD column, two PSS GRAM columns in series (8 mm x 300 mm); column temperature: 50 °C; mobile phase: DMF / FA (2%); flow rate: 1.0 mL / min; injection volume: 100 L; detector: Agilent Refractive Index detector, 50 °C; and calibration curve: PL polyethylene glycol narrow standards with molecular weights ranging from 542500 to 1010 g / mol using a polynom 3 fit.
[0093] Synthesis of Castor Oil Modified Acrylic Copolymer Dispersion A ("Castor Oil Modified PD-A") Sulfated castor oil (255.92 g) and DI water (1,544 g) were added to a three-neck flask reactor. DI water (57 g) and 808 g of monomer (consisting of 84.6% AA / 0.3% ALMA / 15.1% MAA by weight percent) were added with stirring to form a monomer mixture. APS (8.11 g) was dissolved in DI water (158.84 g) to form a catalyst solution. After the reactor was heated to 90° C., the monomer mixture and catalyst solution were added to the reactor over a period of 180 minutes. The reactor was then held at 90° C. for an additional 30 minutes. FeSO4 solution (15.9 g, 0.08%) was added to the reactor. Hydrogen peroxide solution (54.88 g, 5.7%) and IAA solution (103.6 g, 8%) were added to the reactor over a period of 30 minutes. After cooling to room temperature, NaOH solution (103 g, 3.2%) was added to the reactor, and then the resulting emulsion was filtered through a 100 mesh filter to obtain a sulfated castor oil modified acrylic copolymer dispersion (pH value: 2.50, solid content: 33%, and M of the resulting water-based resin). n :26,714g / mol).
[0094] Synthesis of Polymer Dispersion 1 ("PD-1") DI water (2,240 g), AR-1025 surfactant (25%, 336 g), ST (2,887 g), 2-EHA (2,451 g), CHMA (1,747 g), MAA (264 g), PEM (200 g), MEUR (50%, 128 g), and AAEM (232 g) were mixed together to produce a stable monomer emulsion. AR-1025 surfactant (25%, 214 g), ammonia (25%, 4.7 g) in DI water (20 g), monomer emulsion (463 g), and APS (15 g) in DI water (96 g) were added to DI water (5,064 g) under a nitrogen atmosphere at 90° C., followed by DI water (24 g) to form a reaction mixture. The remaining monomer emulsion, APS (9 g) in DI water (400 g), and ammonia (25%, 32 g) in DI water (400 g) were then added over 120 minutes at 88° C., followed by the addition of DI water (25 g). At the end of the polymerization, FeSO4 (0.11 g) in DI water (24 g) mixed with ethylenediaminetetraacetic acid (EDTA) sodium salt (0.14 g) in DI water (24 g), a solution of t-butyl hydroperoxide (t-BHP, 14.7 g) dissolved in DI water (160 g), a solution of IAA (6.5 g) in DI water (160 g), a solution of t-BHP (12.4 g) in DI water (140 g), and a solution of IAA (2.3 g) in DI water (80 g) were added all at 60° C., followed by the addition of ammonia (100 g) in DI water (24 g) at 50° C. to obtain an aqueous polymer dispersion.
[0095] Synthesis of Polymer Dispersion 2 ("PD-2") DI water (2,240 g), AR-1025 surfactant (25%, 336 g), ST (3,119 g), 2-EHA (2,451 g), CHMA (1,747 g), MAA (264 g), PEM (200 g), and MEUR (50%, 128 g) were mixed together to produce a stable monomer emulsion. To DI water (5,064 g) under a nitrogen atmosphere at 90° C., Fes-32 surfactant (31%, 162 g), ammonia (25%, 4.7 g) in DI water (20 g), monomer emulsion (463 g), and APS (15 g) in DI water (96 g) were added, followed by DI water (24 g) to form a reaction mixture. The remaining monomer emulsion, APS (9 g) in DI water (400 g), and ammonia (25%, 32 g) in DI water (400 g) were then added over 120 minutes at 88° C., followed by the addition of DI water (25 g). At the end of the polymerization, FeSO4 (0.11 g) in DI water (24 g) mixed with EDTA sodium salt (0.14 g) in DI water (24 g), a solution of t-BHP (14.7 g) dissolved in DI water (160 g), a solution of IAA (6.5 g) in DI water (160 g), a solution of t-BHP (12.4 g) in DI water (140 g), and a solution of IAA (2.3 g) in DI water (80 g) were added all at 60° C., followed by the addition of ammonia (100 g) in DI water (24 g) at 50° C. to obtain an aqueous polymer dispersion.
[0096] Synthesis of Polymer Dispersion 3 ("PD-3") DI water (2,240 g), AR-1025 surfactant (25%, 336 g), ST (3,760 g), 2-EHA (2,451 g), CHMA (874 g), MAA (264 g), PEM (200 g), MEUR (50%, 128 g), and AAEM (232 g) were mixed together to produce a stable monomer emulsion. AR-1025 surfactant (25%, 214 g), ammonia (25%, 4.7 g) in DI water (20 g), monomer emulsion (463 g), and APS (15 g) in DI water (96 g) were added to DI water (5,064 g) under a nitrogen atmosphere at 90° C., followed by DI water (24 g) to form a reaction mixture. The remaining monomer emulsion, APS (9 g) in DI water (400 g), and ammonia (25%, 32 g) in DI water (400 g) were then added over 120 minutes at 88° C., followed by the addition of DI water (25 g). At the end of the polymerization, FeSO4 (0.11 g) in DI water (24 g) mixed with EDTA sodium salt (0.14 g) in DI water (24 g), a solution of t-BHP (14.7 g) dissolved in DI water (160 g), a solution of IAA (6.5 g) in DI water (160 g), a solution of t-BHP (12.4 g) in DI water (140 g), and a solution of IAA (2.3 g) in DI water (80 g) were added all at 60° C., followed by the addition of ammonia (100 g) in DI water (24 g) at 50° C. to obtain an aqueous polymer dispersion.
[0097] Synthesis of Polymer Dispersion 4 ("PD-4") DI water (2,240 g), Fes-32 surfactant (31%, 271 g), ST (2,636 g), 2-EHA (2,451 g), CHMA (2,316 g), MAA (186 g), PEM (140 g), and MEUR (50%, 128 g) were mixed together to produce a stable monomer emulsion. RS-610 surfactant (25%, 214 g), ammonia (25%, 4.7 g) in DI water (20 g), monomer emulsion (463 g), and APS (15 g) in DI water (96 g) were added to DI water (5,064 g) under a nitrogen atmosphere at 90° C., followed by DI water (24 g) to form a reaction mixture. The remaining monomer emulsion, APS (9 g) in DI water (400 g), and ammonia (25%, 32 g) in DI water (400 g) were then added over 120 minutes at 88° C., followed by the addition of DI water (25 g). At the end of the polymerization, FeSO4 (0.11 g) in DI water (24 g) mixed with EDTA sodium salt (0.14 g) in DI water (24 g), a solution of t-BHP (14.7 g) dissolved in DI water (160 g), a solution of IAA (6.5 g) in DI water (160 g), a solution of t-BHP (12.4 g) in DI water (140 g), and a solution of IAA (2.3 g) in DI water (80 g) were added all at 60° C., followed by the addition of ammonia (100 g) in DI water (24 g) at 50° C. to obtain an aqueous polymer dispersion.
[0098] Synthesis of Polymer Dispersion 5 ("PD-5") DI water (2,240 g), AR-1025 surfactant (25%, 336 g), ST (4,634 g), 2-EHA (2,451 g), MAA (264 g), PEM (200 g), MEUR (50%, 128 g), and AAEM (232 g) were mixed together to produce a stable monomer emulsion. AR-1025 surfactant (25%, 214 g), ammonia (25%, 4.7 g) in DI water (20 g), monomer emulsion (463 g), and APS (15 g) in DI water (96 g) were added to DI water (5,064 g) under a nitrogen atmosphere at 90° C., followed by DI water (24 g) to form a reaction mixture. The remaining monomer emulsion, APS (9 g) in DI water (400 g), and ammonia (25%, 32 g) in DI water (400 g) were then added over 120 minutes at 88° C., followed by the addition of DI water (25 g). At the end of the polymerization, FeSO4 (0.11 g) in DI water (24 g) mixed with EDTA sodium salt (0.14 g) in DI water (24 g), a solution of t-BHP (14.7 g) dissolved in DI water (160 g), a solution of IAA (6.5 g) in DI water (160 g), a solution of t-BHP (12.4 g) in DI water (140 g), and a solution of IAA (2.3 g) in DI water (80 g) were added all at 60° C., followed by the addition of ammonia (100 g) in DI water (24 g) at 50° C. to obtain an aqueous polymer dispersion.
[0099] The properties of the resulting aqueous dispersions PD-1 to PD-5 are shown in Table 1.
[0100] [Table 1] * Solids content was measured according to the test method described above.
[0101] Aqueous polymer compositions of Examples (Ex) 1-2 and 4-6 and Comparative Examples (Comp) 2-4, 7-8, and 10 N,N-dimethylethanolamine (DMEA) (0.72 g) was added to YG-EA670 epoxy ester resin (measured solid content: 75%, 12 g) under stirring. After stirring for 5 minutes, water (12 g) was further added to the resulting mixture under stirring. After the water supply was finished, the mixture was stirred by using a high-speed disperser at 1,000 revolutions per minute (rpm) for 15 minutes to form a solution of water-based epoxy ester resin. Then, the aqueous polymer dispersion prepared above was added to the solution of water-based epoxy ester resin under stirring based on the formulation shown in Table 2 to form an aqueous polymer composition (i.e., a mixture of emulsion polymer and water-based epoxy ester).
[0102] Example 3 RETAN 540 (2.72 g) was added to PD-1 (100 g) and mixed homogeneously to obtain the mixture of Example 3.
[0103] Comparative Example 5 The castor oil-modified PD-A (3.22 g) was added to PD-1 (100 g) and mixed homogeneously to obtain the mixture of Comparative Example 5.
[0104] Comparative Example 6 DMEA (1.58 g), oleic acid (5 g), and water (25 g) were mixed under stirring. The resulting mixture was added to PD-1 (68.42 g) to obtain Comparative Example 6.
[0105] Comparative Example 9 RETAN 540 (9.23 g) was added to PD-1 (100 g) and then mixed homogeneously to obtain the mixture of Comparative Example 9.
[0106] [Table 2] 1 The percentages, except for Comparative Example 6, refer to the dry weight of the aqueous resin relative to the total dry weight of the aqueous resin and the polymer dispersion. Dry weight (water-based resin) = weight (water-based resin) × solids content (water-based resin); and Dry weight (polymer dispersion) = weight (polymer dispersion) x solids content (polymer dispersion). The percentages in Comparative Example 6 refer to the weight of oleic acid relative to the total weight of oleic acid and the dry weight relative to the polymer dispersion. 2 The solids content of the aqueous polymer composition was calculated based on the concentration and solids content of the water-based resin and polymer dispersion in the aqueous polymer composition.
[0107] paint formulation The above obtained aqueous polymer compositions of Examples 1-6 and Comparative Examples 1-10 were used as binders to prepare paint formulations of Paints 1-6 and Comparative Paints 1-10, respectively, based on the formulations shown in Tables 3 and 4. The ingredients in Grind-1 and Grind-2 were prepared using a high-speed disperser (mixing speed: 800-3,000 rpm) to form Grind-1 and Grind-2, respectively. The resulting grinds were mixed with binder using a conventional laboratory mixer (mixing speed: 50-1,000 rpm) and subsequently mixed with other ingredients in the let-down stage. The specific binder compositions, as well as the loadings of binder, Texanol and water used in the let-down stage for each paint formulation, are listed in Table 4. The properties of the resulting paint formulations were evaluated according to the test methods described above, and the results are shown in Table 4.
[0108] As shown in Table 4, after 130 hours of salt spray resistance (SSR) testing, all paints containing binders of Examples 1-6 showed good corrosion resistance, as indicated by creep along the scribe of 2 mm or less. The binders of Examples 1-5 also provided paints with good initial water resistance of grade 10. In contrast, the paint containing PD-1 as the only binder (Comparative Example 1) was unable to meet the creep requirement (i.e., ≦2 mm). Binders whose emulsion polymers did not contain structural units of AAEM (Comparative Example 3), did not contain structural units of CHMA (Comparative Example 4), or contained 30% CHMA (Comparative Example 10) all provided paints with poor corrosion resistance, as indicated by creep along the scribe of much greater than 2 mm. The binder of Comparative Example 5 containing castor oil modified PD-A was unable to provide a paint with corrosion resistance that met the creep requirement. The binder of Comparative Example 6 containing 5% oleic acid was unable to provide a paint with the desired corrosion resistance. Binders containing 15%, 8%, or 0.5% dry weight YG-EA670 (Comparative Examples 2, 7, and 8) or 8% dry weight RETAN 540 (Comparative Example 9) all provided coatings with creep in the scribe greater than 2 mm after SSR testing. Compared to the binder of Example 1, the binder of Comparative Example 2 provided coatings with poor initial water resistance.
[0109] [Table 3]
[0110] [Table 4]
Claims
1. (A) an emulsion polymer, comprising, based on the weight of said emulsion polymer: 5% to 28% by weight of cycloalkyl(meth)acrylate structural units; 0.1% to 10% by weight of acetoacetoxy or acetoacetamido functional monomeric structural units; 0.05% to 10% by weight of structural units of phosphorous acid monomers, salts thereof, or mixtures thereof; 0 to 10% by weight of additional ethylenically unsaturated acid monomer structural units, and 42% to 94% by weight of additional ethylenically unsaturated nonionic monomer structural units an emulsion polymer comprising (B) a water-based resin comprising 0.7% to 7.8% by dry weight, based on the total dry weight of the emulsion polymer and the water-based resin, of at least one fatty acid ester segment and having a number average molecular weight of 20,000 grams / mole or less; 1. An aqueous polymeric composition comprising:
2. 10. The waterborne polymeric composition of claim 1, wherein the waterborne resin is selected from the group consisting of waterborne epoxy esters, unsaturated fatty acid ester modified acrylic copolymers, or mixtures thereof.
3. 3. The aqueous polymeric composition of claim 2, wherein said unsaturated fatty acid ester-modified acrylic copolymer comprises 20% or more by weight of structural units of (meth)acrylic acid, based on the weight of said unsaturated fatty acid ester-modified acrylic copolymer.
4. 3. The waterborne polymeric composition of claim 2, wherein said unsaturated fatty acid ester modified acrylic copolymer is a castor oil or sulfated castor oil modified acrylic copolymer.
5. 3. The waterborne polymeric composition of claim 2, wherein the waterborne epoxy ester comprises the reaction product of an unsaturated fatty acid, and optionally an additional carboxylic acid group-containing compound, and an epoxy compound.
6. 6. The waterborne polymeric composition of claim 5, wherein the waterborne epoxy ester is a (meth)acrylic acid functionalized waterborne epoxy ester.
7. The aqueous polymeric composition of any one of claims 1 to 6, wherein the phosphorous acid monomer is selected from the group consisting of phosphoethyl methacrylate, phosphoethyl acrylate, allyl ether phosphate, or mixtures thereof.
8. 8. The aqueous polymer composition of claim 1, wherein the emulsion polymer comprises, based on the weight of the emulsion polymer, 10% to 25% by weight of structural units of the cycloalkyl (meth)acrylate, 1.5% to 4% by weight of structural units of the acetoacetoxy or acetoacetamide functional monomer, 1.5% to 4% by weight of structural units of the phosphorous acid monomer, its salt, or mixtures thereof, 0 to 10% by weight of structural units of the additional ethylenically unsaturated acid monomer, 55% to 85% by weight of structural units of the additional ethylenically unsaturated nonionic monomer, and optionally 0 to 3% by weight of structural units of an ethylenically unsaturated functional monomer having one or more functional groups selected from ureido, amido, amino, silane, hydroxyl, or combinations thereof.
9. A method for preparing the waterborne polymer composition according to any one of claims 1 to 8 by mixing said emulsion polymer with said waterborne resin.
10. A coating composition comprising the aqueous polymer composition according to any one of claims 1 to 8 and optionally a pigment.
Citation Information
Patent Citations
Aqueous composition and method for preparing non-yellowing coating
JP2004263173A
Method for producing aqueous resin dispersion
JP2006052295A
Curable aqueous resin composition
JP2008074974A
Alkali-proof binder resin composition
JP2009235139A
Aqueous polymer dispersion and aqueous coating composition containing same
JP2022508014A